The Difficulty of Learning Long-Term Dependencies with Gradient Flow in Recurrent Nets - Bynagari , Naresh Babu (Engineering International, 2020)
In theory, recurrent networks (RN) can leverage their feedback connections to store activations as representations of recent input events. The most extensively used methods for learning what to put in short-term memory, on the other hand, take far too long to be practicable or do not work at all, especially when the time lags between inputs and instructor signals are long. They do not provide significant practical advantages over, the backdrop in feedforward networks with limited time windows, despite being theoretically fascinating. The goal of this article is to have a succinct overview of this rapidly evolving topic, with a focus on recent advancements. Also, we examine the asymptotic behavior of error gradients as a function of time lags to provide a hypothetical treatment of this topic. The methodology adopted in the study was to review some scholarly research papers on the subject matter to address the difficulty of learning long-term dependencies with gradient flow in recurrent nets. RNNs are the most general and powerful sequence learning algorithm currently available. Unlike Hidden Markov Models (HMMs), which have proven to be the most successful technique in a variety of sequence processing applications, they are not limited to discrete internal states and can represent continuous, dispersed sequences. As a result, they can address problems that no other method can. Conventional RNNs, on the other hand, are difficult to train due to the problem of vanishing gradients.